Catch Rate and Fish Catch of Boat Lift Net on Different Position in Palabuhanratu Bay Water, Sukabumi, Indonesia - Izza Mahdiana Apriliani; Indah Riyantini; Emma Rochima; M Fahmi Ikmal (JURNAL PERIKANAN DAN KELAUTAN, 2018)
The waters of Palabuhanratu Bay known as the main fishery base in Southern Java Indonesia because dynamical of oceanography influenced by the Indian Ocean. The common fishing gear used in these waters is the lift net, utilizing the phototactic properties of the fish. To determine the catch rate of lift net, focus of this study is to assess the catches with two different fishing areas of lift net with the coordinates of 07° 00' 00.6